2018
DOI: 10.1016/j.ceca.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of histamine-evoked Ca2+ signals by compartmentalized cAMP in human bronchial airway smooth muscle cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…It is therefore possible that the two events occur simultaneously. Interestingly, Dale et al (47) are able to observe an effect on histamine but not on other Ca 2ϩ -mobilizing agents, suggesting a certain degree of specificity. Preliminary data from our lab also shows that the mito-hTAS2R46 regulates mitochondrial calcium buffering chondrial uptake increase is not evident when carbachol or bradykinin are used to induce Ca 2ϩ mobilization.…”
Section: Htas2r46 Regulates Mitochondrial Calcium Bufferingmentioning
confidence: 95%
See 1 more Smart Citation
“…It is therefore possible that the two events occur simultaneously. Interestingly, Dale et al (47) are able to observe an effect on histamine but not on other Ca 2ϩ -mobilizing agents, suggesting a certain degree of specificity. Preliminary data from our lab also shows that the mito-hTAS2R46 regulates mitochondrial calcium buffering chondrial uptake increase is not evident when carbachol or bradykinin are used to induce Ca 2ϩ mobilization.…”
Section: Htas2r46 Regulates Mitochondrial Calcium Bufferingmentioning
confidence: 95%
“…Recently, Dale et al (47) have shown that in human bronchial airway smooth muscle cells, histamine-induced cytosolic Ca 2ϩ rises may be blunted by isoproterenol and proposed a model by which compartmentalized cAMP rises negatively feedback via PKA to the histamine receptor. In our study, we were unable to determine the absolute level of Ca 2ϩ released and therefore cannot rule out that IP 3 formation from histamine activation is reduced upon TAS2R46 activation.…”
Section: Htas2r46 Regulates Mitochondrial Calcium Bufferingmentioning
confidence: 99%
“…The change in intracellular Ca2+ concentration was represented by the change of fluorescence intensity. The ratio of fluorescence intensity (F/F0) was used to compare intracellular Ca2+ concentration under different treatments (F: the average fluorescence intensity under different treatments, F0: the initial fluorescence intensity) (Dale et al, 2018;Zhu et al, 2018).…”
Section: Measurements Of [Ca2+]i and Store-operated Calcium Entrymentioning
confidence: 99%
“…Activation of adenylate cyclase (AC) and subsequent increase in the production of cyclic adenosine monophosphate (cAMP) involves the interaction of β‐adrenergic receptor with guanosine triphosphate (GTP) binding proteins such as Gs and Gi, which allows functional coupling of the receptor. Formation of cAMP by AC is important in a variety of physiological and pathological events (Houslay, 1991; Chakraborti et al, 2000; Dale et al, 2018).…”
Section: Introductionmentioning
confidence: 99%